Do Academic Supervisors Know What Their Employees Want from Work? - John C Griffith Ph.D. (Academic Chairpersons Conference Proceedings, 2022)
Presenter will discuss the results of a survey which included respondents from the 2020 Academic Chairperson’s Conference on what employees want from work. Results were compared between what employees valued and what supervisors thought employees wanted from work. Conference participants will be asked to consider how the 10 work factors evaluated in this study impact their employees to include faculty. Additionally, we will discuss strategies focusing on key work factors to improve motivation.
Keywords: Employee motivation; faculty motivation; distance learning administration; human relations; leadership